Distributions and Determinants of Neonatal Mortality in Rembang Regency, Central Java Province, Indonesia - Sani Rachman Soleman; Yovita Oga Odelia (Unnes Journal of Public Health, 2023)
Neonatal mortality in Rembang regency, Central Java province, has raised concerns to solve comprehensively. This study aimed to observe distributions and examine determinants of neonatal mortality in the Rembang regency. A case-control study was conducted to examine 50 cases and 50 control by the medical records in the Department of Health. There were 11 variables: parity, mother's age, gestational age, a congenital defect, neonatal sepsis, neonatal asphyxia, pregnancy complication, birth weight, labour locations, childbirth helper, and type of labour. The analysis consists of bivariate with chi-square and multivariate by logistic regression. The most frequent risk factors are gestational age (P=0.00; OR=18.4; and CI=5.04-67.00) and birth weight (P=0.00; OR=14.7 and CI=4.96-43.51), yet logistic regression found high-risk birth weight (P=0.01; aOR=5.4 and CI=1.43 – 20.34) and high-risk gestational age (P=0.03; aOR=5.8 and CI=1.22-27.59) are significant on neonatal mortality in Rembang regency, Central Java Indonesia. This finding is essential in taking policy action on safe pregnancy among high-risk women in the Rembang regency.